PENGETAHUAN DAN SIKAP PERAWAT TENTANG KOMUNIKASI TERAPEUTIK DI PUSKESMAS PANDERE KECAMATAN GUMBASA KABUPATEN SIGI - Wahyu (Sekolah Tinggi Ilmu Kesehatan Indonesia Jaya Palu, 2023)
Therapeutic communication improves interpersonal relationships with patients so that a conducive at-mosphere is created where patients can express their feelings and hopes. Nurses have the longest contact in dealing with client problems through therapeutic communication. The results of interviews at the Pandere Health Center, Gumbasa District, Sigi Regency with patients said that there were still many nurses who lacked therapeutic communication. The purpose of this study was to find out the knowledge and attitudes of nurses about therapeutic communication at the Pandere Health Center, Gumbasa District, Sigi Regency. The type of research used is descriptive research. The variables in this study are the knowledge and attitudes of nurses about therapeutic communication. The data used are primary data and secondary data. Data analysis using univariate analysis. The population and sample in this study were 16 nurses. The results showed that 13 nurses (81.2%) had good knowledge of therapeutic communication, while 3 nurses (18.8%) had poor knowledge. A good attitude is 7 nurses (43.7%), enough is 8 nurses (50%) while 1 nurse lacks attitude. (6.3%). The conclu-sion of this study is that most nurses at the Pandere Health Center, Gumbasa District, Sigi Regency have good knowledge and attitudes about therapeutic communication. It is expected that nurses can maintain good nurse knowledge and attitudes about therapeutic communication, given training on therapeutic communication.